Effect of Fennel Aromatherapy (Foeniculum Vulgare) On Decreasing Menopause Symptom Levels in Menopausal Women in Tunjung Village Bangkalan Regency Indonesia - Selly Sutardi; Ervi Husni; Elfira Nurul Aini; K. Kasiati; Kanwaljeet Kaur (International Journal of Advanced Health Science and Technology, 2022)
Menopause is a natural event in a woman's life cycle. Hormonal changes that occur during menopause cause more than 80% of women to experience symptoms both physical and psychological with various pressures and disorders, causing a decrease in the quality of life. One of the non-pharmacological treatments to reduce the level of menopausal symptoms is Fennel aromatherapy. This study aims to determine the effect of Fennel Aromatherapy on reducing the level of menopausal symptoms. This type of research is Quasy Experimental with Non-Equivalent Control Group Design. The population of postmenopausal women aged 45-55 years is 62 people. Samples were taken using the purposive sampling technique of 22 people per group. The instrument used is the MRS (Menopause Rating Scale) questionnaire. statistical test using Wilcoxon Matched Pairs Test with α 0.05. The results showed that most menopausal women (68.2%) from the control group and most menopausal women (72.7%) from the treatment group had severe menopausal symptoms. After being given the intervention, there was a decrease in the treatment group where half of menopausal women (50.0%) had moderate levels of menopausal symptoms. The results of the analysis obtained p-value 0.000058 or <α (0.05) which means that there is an influence of Fennel Aromatherapy (Foeniculum Vulgare) on decreasing the level of menopausal symptoms. This research can add alternative treatment for menopausal symptoms in the BATRA program at community health centers. It is hoped that postmenopausal women can use safe alternative therapies such as Fennel Aromatherapy to treat menopausal symptoms so that it can improve the quality of life of women during menopause without serious side effects.